Scavenging and fractionation of particle-reactive radioisotopes 7Be, 210Pb and 210Po in the atmosphere. (1st September 2016) - Chen, Jinfang; Luo, Shangde; Huang, Yipu
Abstract: The scavenging and fractionation of 7 Be, 210 Pb, and 210 Po in the atmosphere are investigated by measuring their activities in rainwater collected from 68 rain events during March 2004 to April 2006 at a coastal station of Xiamen, southeastern China. In addition to documenting the large temporal variations in activities, fluxes, and isotope ratios of 7 Be, 210 Pb and 210 Po in rainwater and the role of rainfall intensity in radionuclide scavenging, our results show that an enhanced deposition of 7 Be and 210 Pb occurs in the spring than in other seasons and is attributed to the "funnel effect" due to the increased atmospheric vertical convective mixing in the spring. This latter hypothesis is further supported by the observed seasonal and inter-annual variations in 7 Be/ 210 Pb and 210 Po/ 210 Pb ratios showing that the weakening of vertical convective mixing or stratosphere–troposphere exchange (STE) at the study site is linked with the enhancement of summer monsoons. It appears that the rainfall intensity, in connection with the vertical (e.g., STE) and horizontal (summer monsoons) air transport, exerts an important control on the activities, fluxes, and isotope ratios of 7 Be, 210 Pb, and 210 Po in the atmosphere. Application of the observational data to a theoretical model shows that there are significant fractionations among 7 Be, 210 Pb, and 210 Po in the atmosphere, with the scavenging rate constant or reciprocal of the residence time of radionuclide in the atmosphere being 210 Pb >  7 Be >  210 Po. A revised Poet et al. (1972)'s method is proposed for quantitative constraint on the scavenging behavior of radionuclide, aerosols, and aerosol-associated trace pollutants in the atmosphere.